Design Of Information Technology (IT) Governance Using Framework Cobit 2019 Subdomain APO01 - Mezan el-Khaeri Kesuma; Ricco Herdiyan Saputra; Muhammad Adie Syaputra; Muhammad Reza Romahdoni (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
The purpose of this research is to apply the 2019 Cobit Framework to build an IT Governance design in Instidla. This research belongs to the type of descriptive qualitative research. The method used in making this system is to analyze the relationship of the state of the data and collect data by field research methods, namely by conducting interviews, literature studies and questionnaires. Based on the results of the capability level obtained and the target level as expected, it can be concluded that the gap analysis in the APO01 process is at level 1, which means that the Instidla process more or less achieves its objectives through the implementation of a series of activities that are incomplete or not very organized.